The Activated Macrophage – A Tough Fortress for Virus Invasion: How Viruses Strike Back - Banete, Andra; Barilo, Julia; Whittaker, Reese; Basta, Sameh (Frontiers in Microbiology, 2022)
Macrophages (Mφ) are innate immune cells with a variety of functional phenotypes depending on the cytokine microenvironment they reside in. Mφ exhibit distinct activation patterns that are found within a wide array of activation states ranging from the originally discovered classical pro-inflammatory (M1) to the anti-inflammatory (M2) with their multi-facades. M1 cells are induced by IFNγ+LPS, while M2 are further subdivided into M2a (IL-4), M2b (Immune Complex) and M2c (IL-10) based on their inducing stimuli. Not surprisingly, Mφ activation influences the outcome of viral infections as they produce cytokines that in turn activate cells of the adaptive immune system. Generally, activated M1 cells tend to restrict viral replication, however, influenza and HIV exploit inflammation to support their replication. Moreover, M2a polarization inhibits HIV replication at the post-integration level, while HCMV encoded hrIL-10 suppresses inflammatory reactions by facilitating M2c formation. Additionally, viruses such as LCMV and Lassa Virus directly suppress Mφ activation leading to viral chronicity. Here we review how Mφ activation affects viral infection and the strategies by which viruses manipulate Mφ polarization to benefit their own fitness. An understanding of these mechanisms is important for the development of novel immunotherapies that can sway Mφ phenotype to inhibit viral replication.